Ergogenic aids - Leutholtz, Brian C; American College of Sports Medicine (Monterey, CA : Healthy Learning, 2006)
Presents a review of the most up-to-date scientific information available on 15 of the most popular ergogenic aids. This DVD offers an easy-to-understand discussion of which ergogenic supplements are effective and which ones are not-- and why
Title from title screen
Keywords: Dietary supplements -- Sports; Health; Physical fitness